Bio-waste-derived hydroxyapatite from fish bone, bovine bone, and bovine teeth for enamel remineralization - Chawan Karim Jabar; Hadi M. Ismail (Frontiers in Oral Health, 2026)
Objectives To investigate whether calcined fish bone, bovine bone, and bovine teeth can be converted into bioactive hydroxyapatite powders, and whether these materials can function as slurries and promote the remineralization of enamel. The novelty of this study is the production of hydroxyapatite from biowaste-derived bovine bone and bovine teeth powders, and its use as remineralizing agents for demineralized enamel for the first time. Methods Eighty-four human premolar enamel specimens were allocated into seven groups ( n = 12). The physical and chemical properties were done for calcined biowaste materials. Experimental groups were treated with slurries prepared from FiB, BoB, and BoT, while control groups included TM, demineralized enamel, non-protected enamel, and sound enamel. Remineralization was assessed using SEM, EDX, and AFM. Results Characterization confirmed the hydroxyapatite-like structures formation with Ca/P ratios varying from 1.55 to 1.64, mesoporous architecture (10–20 nm), and variable crystallinity. The experimental groups had higher calcium content and Ca/P ratio comparing to the negative control group ( p < 0.05), was very close to that in TM group and sound enamel. The SEM showed in treated enamel surfaces were smoother with clear crystal deposits, especially in the BoT group. Treated enamel surface in the BoT group showed less porosity and a more uniform surface. AFM analysis showed that surface roughness in the BoT and TM groups was significantly reduced ( p < 0.05), such as Sq value in TM group decreased from 33.6 nm to 10.2 nm. Conclusion The calcined biowaste-derived HAp materials showed an improvement in the remineralization of enamel, and the bovine tooth-derived HAp had the best overall performance.